Ali Goes Travelling - Thom, Patience (University Press Plc, 1992)
This book is about a boy called Ali, who lives in a big city in Nigeria. Ali likes living in a city. He likes watching the people, animals and cars, which pass his father's house every day. He goes to school in the middle of the city. Sometimes he runs to school in the morning. If he is the first in his class to arrive, he cleans the blackboard for his teacher...
Keywords: Juvenile Fiction / Adventure